Combined Inhibition of EZH2 and FGFR is Synergistic in BAP1-deficient Malignant Mesothelioma - Badhai, Jitendra; Landman, Nick; Pandey, Gaurav Kumar; Song, Ji-Ying; Hulsman, Danielle; Krijgsman, Oscar; Chandrasekaran, Gayathri; Berns, Anton; van Lohuizen, Maarten (Cancer research communications, 2024)
Malignant mesothelioma is a highly aggressive tumor with a survival of only 4-18 months after diagnosis. Treatment options for this disease are limited. Immune checkpoint blockade using ipilimumab and nivolumab has recently been approved as a frontline therapy, but this led to only a small improvement in overall patient survival. As more than half of patients with mesothelioma have alterations in the gene encoding for BAP1 this could be a potential marker for targeted therapies. In this study, we investigated the synergistic potential of combining EZH2 inhibition together with FGFR inhibition for treatment of BAP1-deficient malignancies. The efficacy of the combination was evaluated using human and murine preclinical models of mesothelioma and uveal melanoma in vitro. The efficacy of the combination was further validated in vivo by using BAP1-deficient mesothelioma xenografts and autochthonous mouse models. In vitro data showed sensitivity to the combined inhibition in BAP1-deficient mesothelioma and uveal melanoma tumor cell lines but not for BAP1-proficient subtypes. In vivo data showed susceptibility to the combination of BAP1-deficient xenografts and demonstrated an increase of survival in autochthonous models of mesothelioma. These results highlight the potential of this novel drug combination for the treatment of mesothelioma using BAP1 as a biomarker. Given these encouraging preclinical results, it will be important to clinically explore dual EZH2/FGFR inhibition in patients with BAP1-deficient malignant mesothelioma and justify further exploration in other BAP1 loss-associated tumors. Despite the recent approval of immunotherapy, malignant mesothelioma has limited treatment options and poor prognosis. Here, we observe that EZH2 inhibitors dramatically enhance the efficacy of FGFR inhibition, sensitising BAP1-mutant mesothelioma and uveal melanoma cells. The striking synergy of EZH2 and FGFR inhibition supports clinical investigations for BAP1-mutant tumors.